ASUHAN KEPERAWATAN PADA NY.S DENGAN PENERAPAN TERAPI REFLEKSI PIJAT KAKI TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI WILIYAH KERJA PUSKESMAS TIBAN BARU - Fatrida, Dedi; Yudastoro, Fasida Dharma (Ensiklopedia of Journal, 2024)
Abstract: The chronic disease that many elderly people suffer from is hypertension, this disease is one of several important risk factors for cardiovascular diseases such as coronary heart disease, heart failure and stroke. Factors that can cause high blood pressure are age, diet and genetics, causing increased morbidity and mortality. The aim of this research is to describe the results of nursing care using foot massage reflexology therapy to reduce blood pressure in hypertensive elderly in the Tibn Baru Health Center work area on 22 September 2024. The method used in this scientific paper is a case study carried out based on nursing care. Blood pressure is measured using a blood pressure meter. The results of nursing care are the client's condition with the criteria that the problem is resolved. So Dx pain and risk of fall in Mrs. S was resolved, after the foot massage reflexology therapy intervention was carried out by Mrs. S before being given an endorphin massage of TD: 170/100 mmHg and after being given an endorphin massage for 3 days amounted to TD: 130/70 mmHg. Evaluation results Conclusion Foot massage therapy refleks is effective in reducing blood pressure in elderly people with hypertension.Keywords: Hypertension in the elderly, nursing care, foot reflexology massage